2000
DOI: 10.1093/emboj/19.14.3608
|View full text |Cite
|
Sign up to set email alerts
|

Phasic characteristic of elementary Ca2+release sites underlies quantal responses to IP3

Abstract: Ca 2+ liberation by inositol 1,4,5-trisphosphate (IP 3 ) is quantal', in that low [IP 3 ] causes only partial Ca 2+ release, but further increasing [IP 3 ] evokes more release. This characteristic allows cells to generate graded Ca 2+ signals, but is unexpected, given the regenerative nature of Ca 2+ -induced Ca 2+ release through IP 3 receptors. Two models have been proposed to resolve this paradox: (i) all-or-none Ca 2+ release from heterogeneous stores that empty at varying [IP 3 ]; and (ii) phasic liber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 51 publications
(108 reference statements)
3
80
0
Order By: Relevance
“…To then achieve single-channel resolution, we used TIRF imaging of a subset of puff sites located close to the plasma membrane (17), so that rapid binding of Ca 2ϩ to the fast indicator dye within attoliter cytosolic volumes around puff sites yields fluorescence signals that more closely track instantaneous Ca 2ϩ flux through IP 3 R channels (14). Additionally, we gained a further improvement by loading cells with EGTA, a Ca 2ϩ buffer that inhibits wave propagation (17)(18)(19) and accelerates the collapse of the local Ca 2ϩ micro-domain but, because of its slow binding kinetics, minimally perturbs local free [Ca 2ϩ ] within a cluster (14) and has little effect on peak puff amplitudes (17)(18)(19). EGTA is thus…”
Section: Resultsmentioning
confidence: 99%
“…To then achieve single-channel resolution, we used TIRF imaging of a subset of puff sites located close to the plasma membrane (17), so that rapid binding of Ca 2ϩ to the fast indicator dye within attoliter cytosolic volumes around puff sites yields fluorescence signals that more closely track instantaneous Ca 2ϩ flux through IP 3 R channels (14). Additionally, we gained a further improvement by loading cells with EGTA, a Ca 2ϩ buffer that inhibits wave propagation (17)(18)(19) and accelerates the collapse of the local Ca 2ϩ micro-domain but, because of its slow binding kinetics, minimally perturbs local free [Ca 2ϩ ] within a cluster (14) and has little effect on peak puff amplitudes (17)(18)(19). EGTA is thus…”
Section: Resultsmentioning
confidence: 99%
“…Opening events can therefore involve single channels, few or all channels in one cluster, or many channels from several clusters. The different release modes are indeed observed experimentally and termed blip, puff (Yao & Parker, 1995;Callamaras & Parker, 2000), or global release, respectively. The fact that the different modes result from different channel synchronization strengths was studied in many publications and can be summarized as follows.…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…The latter case can appear due to reduced cooperativity of channels in different clusters. It was found that the addition of an exogenous buffer protein (EGTA) compels the transition from global to local release (Callamaras & Parker, 2000). The transition can be understood from the fact that additional buffer reduces the spatial extent of calcium domains, thereby decreasing the amount of Ca 2+ diffusing to adjacent clusters.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations